Urgensitas Maqāsidus Syāriah dalam Transformasi Hybrid Contract pada Lembaga Keuangan Syariah - Ahmad Iqbal Fathoni (Fakultas Syariah dan Ekonomi Islam, Universitas Ibrahimy, 2022)
Along with the times, Islamic Banking is required to always make new and actual breakthroughs in the field of Islamic economic transactions in order to answer current financial needs. Among the many contemporary transactions carried out by Islamic Banking is a hybrid contract or better known as Multi Akad. The transaction seems to be a solution to contemporary financial needs. However, even so, there are still some Islamic economists who doubt the validity of the hybrid contract, so there is a need for a new approach in the perspective of Islamic law in order to answer the doubts of some experts, including Maqasidus Syariah.